Degradation of the antifungal pharmaceutical clotrimazole by UVC and vacuum-UV irradiation: Kinetics, transformation products and attenuation of toxicity. Issue 5 (October 2021) - Gonçalves, Nuno P.F.; del Puerto, Oihane; Medana, Claudio; Calza, Paola; Roslev, Peter
Abstract: Azole fungicides are frequently detected as water contaminants due to extensive societal use, and these broad-spectrum antifungal chemicals can cause harmful effects in non-target organisms. Vacuum ultraviolet (VUV) treatment is an efficient and green technology that produces hydroxyl radical to remove contaminants from water. This study investigated the potential of UVC (254 nm) and combined VUV/UVC (185/254 nm) treatment to remove the widely used antifungal compound clotrimazole from water. Degradation kinetics, degradation mechanisms, and toxicity mitigation were investigated using a VUV photoreactor. Toxicity of clotrimazole to aquatic organisms before and after UV treatment were investigated using the luminescent bacterium Aliivibrio fischeri, the bioluminescent yeast Saccharomyces cerevisiae BLYR, the filamentous fungus Fusarium graminearum, the freshwater microalga Raphidocelis subcapitata, and the crustacean Daphnia magna . VUV irradiation efficiently degraded the persistent pollutant clotrimazole at elevated concentrations (mg/L) and at environmental concentrations (µg/L) with > 50% abatement in 1 min and > 95% removal within 32 min. VUV photolysis produced 8 transformation products manly resulting from drug hydroxylation in the phenyl ring and/or imidazole group followed by ring opening or loss of the imidazole moiety. Substantial decrease in aquatic toxicity was observed after UV treatment suggesting that VUV irradiation of aqueous clotrimazole generated less-toxic transformation products. Graphical Abstract: ga1 Highlights: Vacuum UV and UVC irradiation efficiently removed antifungal clotrimazole from water. Vacuum UV treatment did now require addition of supplementary oxidants or catalysts. Clotrimazole degradation pathways under Vacuum UV irradiation were proposed. Vacuum UV treatment of clotrimazole generated less-toxic transformation products. Toxicity of clotrimazole to a battery of test organisms was reduced after Vacuum UV.